Prehabilitation: preoperative rehabilitation interventions for lung cancer – a scoping review - Colaço, Ana Jesus; Castro, Cidália; Hall, Steven; Fernandes, Júlio Belo (Frontiers in Aging, 2025)
BackgroundIndividuals undergoing lung cancer surgery often face significant postoperative challenges, underscoring the importance of identifying effective preoperative rehabilitation strategies to support recovery.AimTo identify rehabilitation interventions that can be implemented during the preoperative period for individuals with lung cancer undergoing thoracic surgery.DesignScoping review guided by the Arksey and O'Malley methodological framework.MethodsThe research question guiding this review was “What rehabilitation interventions should be implemented in the preoperative period for individuals with lung cancer undergoing surgery?” A comprehensive search was performed across five databases: MEDLINE, Cochrane Central, CINAHL, ScienceDirect, and PubMed. The review included studies that addressed rehabilitation interventions before thoracic surgery for individuals with lung cancer.ResultsA total of 19 articles met the inclusion criteria. The findings indicate that combining aerobic endurance, resistance, and respiratory training with preoperative education improves outcomes. In addition, nutritional counseling and brief relaxation/emotion-regulation strategies appear to be valuable components of multimodal prehabilitation programs, though evidence is limited.ConclusionPreoperative rehabilitation interventions have the potential to enhance functional reserve, reduce postoperative complications, and accelerate recovery in individuals undergoing lung resection for lung cancer.